Integrasi Pembentukan Nilai Karakter Kemandirian Siswa Sekolah Dasar dalam Pembelajaran Matematika di Era Industri 4.0 - Deysti Trifena Tarusu; Zulela Zulela; Adi Apriadi Adiansha (Lembaga Penelitian dan Pendidikan Mandala, 2020)
The importance of integrating the formation of the value of independence character in mathematics learning has a positive influence on the quality of education in Indonesia. The purpose of this qualitative study is to get input on how elementary school teachers are about integrating the value of independence characters in mathematics learning. This type of research uses a qualitative approach with interviews, observation, and documentation with the data validity test used is triangulation. The subjects of this study were classroom teachers and students at Buah Ati Elementary School in Bekasi Regency. The results of the study are 1) The value of the character of independence must be instilled in elementary schools, so students can appear aware of following the school rules and honesty with the students themselves; 2) The formation of the value of the character of independence must be given to children from childhood through education in schools, families, and communities; 3) Positive influence on the formation of the value of the character of independence in Mathematics Learning in the Industrial Age 4.0